Systematic review of studies reporting positive surgical margins after bladder neck sparing radical prostatectomy - Bellangino, M; Verrill, C; Leslie, T; Bell, R; Hamdy, F; Lamb, A (Springer US, 2017)
Bladder neck preservation (BNP) during radical prostatectomy (RP) has been proposed as a method to improve early recovery of urinary continence after radical prostatectomy. However, there is concern over a possible increase in the risk of positive surgical margins and prostate cancer recurrence rate. A recent systematic review and meta-analysis reported improved early recovery and overall long-term urinary continence without compromising oncologic control. The aim of our study was to perform a critical review of the literature to assess the impact on bladder neck and base margins after bladder neck sparing radical prostatectomy.We carried out a systematic review of the literature using Pubmed, Scopus and Cochrane library databases in May 2017 using medical subject headings and free-text protocol according to PRISMA guidelines. We used the following search terms: bladder neck preservation, prostate cancer, radical prostatectomy and surgical margins. Studies focusing on positive surgical margins (PSM) in bladder neck sparing RP pertinent to the objective of this review were included.Overall, we found 15 relevant studies reporting overall and site-specific positive surgical margins rate after bladder neck sparing radical prostatectomy. This included two RCTs, seven prospective comparative studies, two retrospective comparative studies and four case series. All studies were published between 1993 and 2015 with sample sizes ranging between 50 and 1067. Surgical approaches included open, laparoscopic and robot-assisted radical prostatectomy. The overall and base-specific PSM rates ranged between 7-36% and 0-16.3%, respectively. Mean base PSM was 4.9% in those patients where bladder neck sparing was performed, but only 1.85% in those without sparing. Bladder neck preservation during radical prostatectomy may increase base-positive margins. Further studies are needed to better investigate the impact of this technique on oncological outcomes. A future paradigm could include modification of intended approach to bladder neck dissection when anterior base lesions are identified on pre-operative MRI.